Konservasi Semen Ayam Buras Menggunakan Berbagai Pengencer Terhadap Fertilitas Dan Periode Fertil Spermatozoa Pasca Inseminasi Buatan - Ridwan Ridwan; Rusdin Rusdin (Universitas Tadulako, 2008)
The aim of the experiment was to determine spermatozoa fertility and accurate interval time of artificial insemination for improving chicken quality and production. The experiment was conducted using a completely randomized design with three levels of semen diluter as the treatments. Each treatment was tested to 10 local female chicks. The research results showed that the treatments significantly affected the fertility of spermatozoa (P < 0.05). The highest fertility of spermatozoa was found in the ringer lactate diluter (74.73 %), followed by the ringer dextrose (71.58 %), and physiological NaCl 0.9 % (65.79 %). The highest fertility period produced by ringer dextrose diluter was 15.6 days, and ringer lactate for 15.3 days.